2016
DOI: 10.1186/s12879-016-1995-z
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ and health system’s delays in the diagnosis and treatment of new pulmonary tuberculosis patients in West Gojjam Zone, Northwest Ethiopia: a cross-sectional study

Abstract: BackgroundTuberculosis (TB) is a major public health concern in the developing world. Early diagnosis and prompt initiation of treatment is essential for effective TB control. The aim of this study was to determine the length and analyze associated factors of patients’ and health system’s delays in the diagnosis and treatment of new pulmonary TB (PTB) patients.MethodsA cross-sectional study was conducted in 30 randomly selected public health facilities in West Gojjam Zone, Amhara Region, Ethiopia. Newly diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
32
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 27 publications
9
32
1
3
Order By: Relevance
“…Weak TB service delivery system was found as a key constraint to TB control. Consistent with findings of previous studies [5,29,30], integration of TB into general health services was weak. Social stigma and concern for contracting TB meant that health workers refuse deployment to and participation in TB control programmes.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Weak TB service delivery system was found as a key constraint to TB control. Consistent with findings of previous studies [5,29,30], integration of TB into general health services was weak. Social stigma and concern for contracting TB meant that health workers refuse deployment to and participation in TB control programmes.…”
Section: Discussionsupporting
confidence: 90%
“…Poor adherence to GeneXpert algorithm, interrupted supply of cartridges, lack of replacement of damaged modules, poor maintenance, and poor recording and reporting limit usefulness of GeneXpert in TB diagnosis [14,26,27]. Poor adherence to national guidelines [11,22,23]; dilapidated infrastructure [5,12,23] weak TB/HIV integration [10,12,14,24,28]; lack of public-private mix [10,12,23] and poor integration into general health services hinder effective TB service delivery [5,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…We observed a median health system delay of 21 days (10–30 IQR) and the maximum was 365 days. The magnitude of health systems delay observed in other studies in different settings in India ranged from a median of 13 to 54 days [ 18 , 19 , 27 , 28 ] and a median of 5 to 22 days in other countries [ 29 31 ]. Delays in treatment initiation further increase the probability of TB transmission in the community and amongst health professionals.…”
Section: Discussionmentioning
confidence: 96%
“…Our study showed that TB cases who were female, aged 45 years and older, UK-born, resided outside London or had extrapulmonary TB were significantly more likely to have a delay in diagnosis of more than 4 months between onset of symptoms and starting treatment. Studies in similar countries with low TB incidence have described similar factors associated with diagnostic delay; however, none have used national-level data [4][5][6][7][8][9][10][11][12][13][14][15]. There has been one previous study in the UK using national leveldata to assess diagnostic delay among index cases and their contacts within households, which found that there was a median delay of 65 days for index cases and 61 days for subsequent symptomatic cases [16].…”
Section: Discussionmentioning
confidence: 99%